A.R. Bellamy: People, places and things – reflections on a life in science - Smith, Willie (New Zealand Science Review, 2010)
​The massive restructuring of the national science system in 1989 led many scientists to crave a stability that would allow them simply to ‘get on with the job’. The on-going debate on the place of science and research in national development, and the role of the CRIs and the universities suggests such stability remains some way off. Behind this debate is an implicit assumption that policies for science ‘drive’ the system. Professor Dick Bellamy, who retired at the end of 2008 after a long and distinguished career as a research scientist, senior manager, and champion of science, is well positioned to put such changes in perspective.